Dynamics of rhizosphere bacterial communities and soil physiochemical properties in response to consecutive ratooning of sugarcane - Khan, Abdullah; Wei, Yibin; Adnan, Muhammad; Ali, Izhar; Zhang, Muqing (Frontiers in Microbiology, 2023)
Ratooning in sugarcane often leads to soil problems such as degradation, acidification, and soil-borne diseases that negatively impact agriculture output and sustainability. Understanding the alteration in bacterial communities, activities, and their diversity connected to the plant and soil under consecutive ratooning still needs to be clarified. To address this gap, multidisciplinary approaches such as Illumina sequencing, and measurement of soil nutrients and enzymes, we analyzed soil samples in a field with three consecutive ratooning sugarcane crops. Results revealed a decline in crop yield and significant changes (P < 0.05) in soil nutrients and bacterial diversity. Ratooning resulted in an acidic environment that potentially affected soil nutrients and enzyme activity responsible for cycling of carbon, nitrogen, and phosphorous. Non metric dimensional scaling (NMDS) confirmed the effect of ratooning on soil attributes. Moreover, a positive correlation between soil physiochemical properties and soil enzymes was observed. Alpha diversity indices indicated greater bacterial diversity in ratooning sugarcane. Bacterial diversity varied throughout the ratooning crop, and significant (P < 0.05) changes in the relative abundance of specific phyla were observed. For example, the relative abundance of Proteobacteria was decreased and Acidobacteria was increased. Furthermore, the relative abundance of bacterial phyla was strongly correlated with soil attributes (enzymes and nutrients). Additionally, ratooning results in the depletion or enrichment of important agriculture microbial genera such as Sphingomonas, Burkholderia, and Acidothermus (P < 0.05), respectively. In conclusion, ratooning led to soil acidification, decreased fertility, and altered microbial structure and activity. Thus, restraining soil acidity by means of liming or biofertilizers to maintain soil nutrients, enzymatic activities, and microbial structure could benefit plants and soil to help create a long-term eco-friendly sugarcane cropping system.